Physical and physiological demands of competitive badminton across performance levels, sex, and age: a systematic review (2020–2026) - Eval Edmizal; Rezha Arzhan Hidayat; Rudyanto Rudyanto; Jeki Haryanto (Lentera Negeri, 2026)
The Scopus database was thoroughly searched by applying a Boolean search strategy that combined badminton, physical fitness, physiological demands, match analysis, and performance determinants related terms. Two reviewers independently screened titles, abstracts, and full texts and extracted the data, with disagreements resolved by a third reviewer, and the methodological quality of eligible studies was appraised using the FICO framework (Focus, Information, Context, Outcome). The thematic re-interpretation has uncovered four major areas of research: (1) the aerobic and anaerobic physiological profiling of players at different competitive levels; (2) biomechanical and neuromuscular features related to stroke mechanics and footwork; (3) training programs to increase explosive power, core stability, and agility; and (4) injury patterns and competition recovery monitoring. The results show that badminton performance stands on a complex interplay of a high-intensity intermittent exercise capacity, the ability of the lower limbs to generate explosive power, the velocity of the upper-body strokes, and the agility that is based on quick reactions. Training strategies incorporating plyometric, weight lifting, and balance exercises simultaneously have shown to have positive effects on performance consistently. Quantitatively, top-tier male players generally achieve a maximum oxygen uptake of around 55-68 mL/kg/min, on the other hand, integrated training involving plyometric, resistance, and balance exercises for 8-12 weeks led to the most stable improvements in the speed of smash and footwork. The review highlights that in the future research the use of standardized protocols for performance assessment and longitudinal study designs for monitoring should be adopted